2019
DOI: 10.33233/eb.v18i1.2085
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção e cuidados frente às complicações mamárias relacionadas í  amamentação na atenção primária í  saúde

Abstract: Objetivo: Descrever a experiência de ações educativas relacionadas a prevenção e cuidados frente as complicações mamárias referentes ao processo de amamentação. Métodos: Trata-se de um estudo descritivo, de natureza qualitativa, relato de experiência, a partir da vivência da estratégia de educação em saúde com puérperas acompanhadas pela Estratégia Saúde da Família localizada em um município do Ceará, que oferece campo de estágio para um curso de graduação em Enfermagem. A experiência ocorreu durante estágio c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Given the above, considering the relevance of breastfeeding and how it affects the nutritional status of the child, defense against infections, physiology and cognitive and emotional development, as well as having implications for the physical and mental health of the mother, it is essential to evaluate the main complications and problems that are involved with the interruption of breastfeeding, providing the mother and the infant with better conditions for this practice to take place 2,4,6,12 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the above, considering the relevance of breastfeeding and how it affects the nutritional status of the child, defense against infections, physiology and cognitive and emotional development, as well as having implications for the physical and mental health of the mother, it is essential to evaluate the main complications and problems that are involved with the interruption of breastfeeding, providing the mother and the infant with better conditions for this practice to take place 2,4,6,12 .…”
Section: Methodsmentioning
confidence: 99%
“…Fissures are often found in puerperal women, being defined as erosions or cracks in the nipple skin that can cause the destruction of the epidermis layers to the lower layer of the dermis 13,14 . Our study revealed a rate of 60% of fissures in the patients studied during the immediate puerperium and corroborates the high incidence.…”
Section: Fissuresmentioning
confidence: 99%
See 3 more Smart Citations